Comparison of 68Ga-labeled RGD mono- and multimers based on a clickable siderophore-based scaffold - Kaeopookum, Piriya; Petrik, Milos; Summer, Dominik; Klinger, Maximilian; Zhai, Chuangyan; Rangger, Christine; Haubner, Roland; Haas, Hubertus; Hajduch, Marian; Decristoforo, Clemens (Nuclear medicine and biology, 2019)
Cyclic pentapeptides containing the amino acid sequence arginine-glycine-aspartic (RGD) have been widely applied to target αvβ3 integrin, which is upregulated in various tumors during tumor-induced angiogenesis. Multimeric cyclic RGD peptides have been reported to be advantageous over monomeric counterparts for angiogenesis imaging. Here, we prepared mono-, di-, and trimeric cyclic arginine-glycine-aspartic-D-phenylalanine-lysine (c (RGDfK)) derivatives by conjugation with the natural chelator fusarinine C (FSC) using click chemistry based on copper (I)-catalyzed azide-alkyne cycloaddition (CuAAC). The αvβ3 binding properties of 68Ga-labeled mono-, di-, and trimeric c(RGDfK) peptides were evaluated in vitro as well as in vivo and compared with the references monomeric [68Ga]GaNODAGA-c(RGDfK) and trimeric [68Ga]GaFSC(suc-c(RGDfK))3. All 68Ga-labeled c(RGDfK) peptides displayed hydrophilicity (logD = -2.96 to -3.80), low protein binding and were stable in phosphate buffered-saline (PBS) and serum up to 2 h. In vitro internalization assays with human melanoma M21 (αvβ3-positive) and M21-L (αvβ3-negative) cell lines showed specific uptake of all derivatives and increased in the series: mono- < di- < trimeric peptide. The highest tumor uptake, tumor-to-background ratios, and image contrast were found for the dimeric [68Ga]GaMAFC(c(RGDfK)aza)2. In conclusion, we developed a novel strategy for direct, straight forward preparation of mono-, di-, and trimeric c(RGDfK) conjugates based on the FSC scaffold. Interestingly, the best αvβ3 imaging properties were found for the dimeric [68Ga]GaMAFC(c(RGDfK)aza)2.
Keywords: Gallium Radioisotopes; myši; Azides; Copper; nádorové buněčné linie; Cell Line, Tumor; PET/CT; click chemie; Siderophores; Click Chemistry; siderofory; Mice; Animals; alkyny; radioizotopy galia; izotopové značení; zvířata; tkáňová distribuce; měď; Peptides, Cyclic; Isotope Labeling; ženské pohlaví; cyklické peptidy; Polymerization; Female; azidy; Alkynes; Positron Emission Tomography Computed Tomography; Tissue Distribution; polymerizace